2004
DOI: 10.1108/14691930410550345
|View full text |Cite
|
Sign up to set email alerts
|

Assessing intellectual capital creation in regional clusters

Abstract: To provide a theoretical model of the dynamics of intellectual capital creation in regional clusters and in inter-organizational networks. The model has been constructed on the basis of earlier studies, especially system's theoretical interpretation of organizations as knowledge systems, and then applied to the examination of a regional cluster operating in the mechanical wood processing industry in Eastern Finland. Intellectual capital in regional clusters is created by three main knowledge creation activitie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
79
0
5

Year Published

2006
2006
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 95 publications
(89 citation statements)
references
References 43 publications
5
79
0
5
Order By: Relevance
“…Regarding intellectual capital and transfer of knowledge, Pöyhönen and Smedlund (2004) suggested that organizations are most successful when adhering to an organic mode, which emphasizes participation through dialogue. In a discussion about self-managed work teams, Thibodeaux and Faden (1994) found support for organic structures as fundamental for effective control and informational changes among the work group members.…”
Section: The Hypothesesmentioning
confidence: 98%
See 2 more Smart Citations
“…Regarding intellectual capital and transfer of knowledge, Pöyhönen and Smedlund (2004) suggested that organizations are most successful when adhering to an organic mode, which emphasizes participation through dialogue. In a discussion about self-managed work teams, Thibodeaux and Faden (1994) found support for organic structures as fundamental for effective control and informational changes among the work group members.…”
Section: The Hypothesesmentioning
confidence: 98%
“…Regarding knowledge intensive organizations, Horwitz et al (2003) concluded that trust, along with other variables, is essential for turning tacit knowledge to explicit knowledge, which is important in building both intellectual and social capital that is accessible by others in the organization. Trust has also been cited as a significant consideration with reference to the learning organization (Ferguson-Amores et al, 2005), for development networks with the purpose of sharing knowledge (Pöyhönen and Smedlund, 2004), and to allow employees to participate in decision making (Puč _ etait_ e and Lämsä, 2008). With this discussion in mind, we, therefore, offer the following hypothesis:…”
Section: The Hypothesesmentioning
confidence: 99%
See 1 more Smart Citation
“…Whilst there has been some recognition that synergies exist in operating categories of IC together, creating a 17 A Google Scholar advanced search on the phrase 'intellectual capital' plus the words 'dynamic' and 'capabilities' anywhere in the article did not result in 'hits' in many articles outside the management discipline (as at 4 July 2012). Pöyhönen & Smedlund (2004) make this link in a specialist IC journal, however the paper has not been highly cited. The IC book by also makes the link but again this book has not been widely cited.…”
Section: Limited Intersection Of Management and Accounting Literaturesmentioning
confidence: 99%
“…During recent years the discussion on knowledge assets has gained popularity beyond the firm level -i.e., at the level of clusters (Pöyhönen & Smedlund, 2004;Hervas Oliver & Dalmau Porta, 2006), regions (Martins & Viedma, 2006;Schiuma et al, 2008) and nations (Bontis, 2004;Lin & Edvinsson, 2008;Ståhle & Bonfour, 2008;Stam & Andriessen, 2009). Regional knowledge assets can be defined as the common knowledge capabilities of regional stakeholders to implement strategies that aim at long-term sustainable development (Kozak, 2011).…”
Section: Regional Knowledge Assets As Drivers Of Knowledge-based Devementioning
confidence: 99%